The effects of bone morphogenetic protein-2 and enamel matrix derivative on the bioactivity of mineral trioxide aggregate in MC3T3-E1cells - Youngdan Jeong; Wonkyung Yang; Hyunjung Ko; Miri Kim (Korean Academy of Conservative Dentistry, 2014)
Objectives The effects of bone morphogenetic protein-2 (BMP-2) and enamel matrix derivative (EMD) respectively with mineral trioxide aggregate (MTA) on hard tissue regeneration have been investigated in previous studies. This study aimed to compare the osteogenic effects of MTA/BMP-2 and MTA/EMD treatment in MC3T3-E1 cells. Materials and Methods MC3T3-E1 cells were treated with MTA (ProRoot, Dentsply), BMP-2 (R&D Systems), EMD (Emdogain, Straumann) separately and MTA/BMP-2 or MTA/EMD combination. Mineralization was evaluated by staining the calcium deposits with alkaline phosphatase (ALP, Sigma-Aldrich) and Alizarin red (Sigma-Aldrich). The effects on the osteoblast differentiation were evaluated by the expressions of osteogenic markers, including ALP, bone sialoprotein (BSP), osteocalcin (OCN), osteopontin (OPN) and osteonectin (OSN), as determined by reverse-transcription polymerase chain reaction analysis (RT-PCR, AccuPower PCR, Bioneer). Results Mineralization increased in the BMP-2 and MTA/BMP-2 groups and increased to a lesser extent in the MTA/EMD group but appeared to decrease in the MTA-only group based on Alizarin red staining. ALP expression largely decreased in the EMD and MTA/EMD groups based on ALP staining. In the MTA/BMP-2 group, mRNA expression of OPN on day 3 and BSP and OCN on day 7 significantly increased. In the MTA/EMD group, OSN and OCN gene expression significantly increased on day 7, whereas ALP expression decreased on days 3 and 7 (p < 0.05). Conclusions These results suggest the MTA/BMP-2 combination promoted more rapid differentiation in MC3T3-E1 cells than did MTA/EMD during the early mineralization period.